Indian Ocean and cultural interaction, A.D. 1400-1800 - Mathew, Kuzhippalli Skaria 1939-.; Pondicherry University (Pondicherry Pondicherry University, 1996)
Contributed articles.
Keywords: Indian Ocean Region -- Ethnic relations